AN INVESTIGATION OF FADS AND ELOVL GENETIC VARIANTS ON RESPONSE TO PUFA-ENRICHED DIETS IN ACUTE RESPIRATORY DISTRESS SYNDROME - Dosso, Beverly (Wake Forest University, 2021)
Background: The use of immunomodulatory diets containing polyunsaturated fatty acids (PUFAs) like y-linolenic acid (GLA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) are inconsistent in patient populations suffering from acute respiratory distress syndrome (ARDS). We postulate that genetic variants impacting PUFA metabolism might explain mixed responses to PUFA-enriched diets.Objective: In this study, we tested the effects of single nucleotide polymorphisms (SNPs) spanning the fatty acid desaturase (FADS) genes and elongase of very long chain fatty acid (ELOVL) genes on differential responses to PUFA-enriched diets in ARDS patients. Design: We performed a secondary analysis of the OMEGA trial (NCT00609180; n=129 control; n=143 omega-oil). DNA was used to genotype 30 FADS-related SNPs and 20 ELOVL SNPs; plasma was used to quantitate PUFA levels. We tested for SNP-diet interactions on PUFA metabolic traits and patient outcomes. Adjustments for multiple comparisons were made, such that a p-value≤<0.003 was considered statistically significant. All statistical analyses were performed in SAS (v9.4, Cary, NC, USA). Results: We determined no single SNP explained the variability in circulating PUFA levels. However, 6 genetic variants were associated with basal estimates of desaturase (as quantified by GLA/LA ratios and ARA/DGLA ratios) and elongase (as quantified by DGLA/GLA and DPA/EPA ratios) activity (i.e. rs174537 (MYRF), rs174532 (MYRF), rs174602 (FADS2), rs174627 (FADS2), rs1346602 (ELOVL5), rs911196 (ELOVL2)). Five genetic variants were marginally associated with inflammatory phenotypes (i.e. rs174537 (MYRF), rs174448 (FADS3), rs7755145 (ELOVL2), rs7760683 (ELOVL2), rs4394207 (ELOVL5)). Two genetic variants were associated with coagulation and hepatic outcomes (i.e. rs498793 (FADS2), rs4532436 (ELOVL2)). Some of these SNPs (i.e. rs174532 (MYRF), rs174602 (FADS2), rs2281591 (ELOVL2), rs1346602 (ELOVL5)) were also associated with mortality in patients receiving the omega-oil diet. Overall, minor allele carriers of FADS variants and ELOVL SNPs tended to display less inflammation and improved patient outcomes with the OMEGA diet. These effects varied drastically by race; with African Americans being more susceptible to worse outcomes. Conclusions: This study highlights key FADS and ELOVL variants potentially associated with PUFA metabolic traits and clinical outcomes in ARDS patients receiving PUFA-enriched diets, as well as potential health disparities between Caucasian and Africans. We confirmed that rs174537 was associated with surrogate measures of FADS1 activity (i.e. ARA/DGLA ratio). We also identified 4 FADS-related SNPs significantly associated with surrogate measures of FADS2 activity (i.e. GLA/LA ratio; rs174532 and rs174602), F3-isoprostane (rs174448), as well as hepatic (i.e. rs498793 and rs174448) and coagulation (rs498793) complications. We additionally identified 2 ELOVL SNPs that were significantly associated with hepatic and coagulation failure-free days (i.e. rs4532436) and 30-day mortality (i.e. rs1346602). Further investigations in larger multi-ethnic cohorts are needed to evaluate the mechanistic impact of these SNPs on differential rates of fatty acid metabolism and downstream thrombogenic pathways in ARDS patients. Keywords: PUFA, FADS, MYRF, ELOVL, ARDS, omega-3, GLA, EPA, DHA, SNP-diet interactions, OMEGA trial
Keywords: ARDS; ELOVL; FADS; MYRF; PUFA; SNP-diet interaction